Synthesis and characterisation of gel-derived mullite precursors from rice husk silica - Sembiring, S.; Simanjuntak, W.; Manurung, P.; Asmi, D.; Low, It Meng (Elsevier Ltd, 2013)
The sol-gel synthesis and characterization of mullite precursor derived from rice husk silica and aluminum nitrate hydrate [(Al(NO3)3·9H2O] has been investigated. The samples were characterized using Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD) coupled with Rietveld analysis, and scanning electron microscopy (SEM). FTIR results showed the presence of Si-O-Si, Al-O-Al, and Si-O-Al functional groups, which were associated with mullite, corundum, quartz, and cristobalite, as verified by XRD analysis. It is concluded that mullite formation started at 1150 °C, and its abundance increased rapidly with an increase in temperature from 1150 to 1350 °C, resulting in increased phase content from 30.9 to 67.7 wt%. Although mullite was formed at a low temperature, the complete reaction between corundum and silica to form mullite was not achieved. This finding demonstrated that rice husk silica is a potential alternative raw material for the production of mullite ceramic.